The Effects of Midazolam Pretreatment on the Induction Dose of Propofol in Nigerian Adults - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:The standard induction dose (2.5 mgkg−1) of propofol in some patients, especially the elderly can result in cardiopulmonary depression often associated with delayed recovery from anaesthesia. Pretreatment with a small dose of sedative or anaesthetic agent prior to administration of induction agent reduces the dose and adverse effects of the required agent.Objectives:This study compared the effects of midazolam pre-treatment on the induction dose of propofol and aimed to determine the following: (1) The induction dose of propofol in patients with midazolam pre-treatment and those on placebo. (2) The time of induction of anaesthesia using propofol in midazolam pre-treated adults. (3) To compare haemodynamic variations in placebo and midazolam pre-treatment groups. (4) The incidence of complications in both the groups.Materials and Methods:Eighty American Society of Anesthesiologits grade I and II patients aged 18–55 years were enrolled and randomly allocated into two groups (A and B) of 40 each. Two minutes before induction of anaesthesia, group A received 0.02 mgkg−1of intravenous midazolam whereas group B received equivalent amount of intravenous 0.9% saline. In both the groups, anaesthesia was induced with propofol using syringe pump at 70 mgmin−1until loss of verbal contact (LOVC) was achieved. The time to reach LOVC and the corresponding amount given were noted. Haemodynamic parameters were recorded at 60 s intervals for 5 minutes afterwards.Results:Midazolam pre-treatment significantly reduced the induction dose requirement of propofol and induction time (P< 0.0001). The incidence of adverse effects of propofol such as hypotension, apnoea and injection pain was significantly higher in the control group (P= 0.03).Conclusion:Midazolam pre-treatment effectively reduces both the induction dose of propofol and time of induction, as well as results in better haemodynamic stability and fewer adverse effects.